REVIEW OF CATTLE MONITORING SYSTEM USING WIRELESS NETWORK (International Journal of Engineering and Computer Science, 2017)
The cattle industry is an integral part of the world economy. The continued production of quality beef requires new and improved methods for long term monitoring of animal health. Additional benefits can be realized from this class of technology, such as the ability to identify the presence of disease early and thereby prevent its spread. An important element of health assessment is the ability to monitor vital data such as core body temperature. This paper reviews other cattle monitoring systems and the importance of employing wireless sensor networks for monitoring cattle core body temperature and location in the ranches along with their advantages and disadvantages.